Usulan Perancangan Ulang Kursi Kerja Ergonomis pada Pekerja Jahit Karung Jumbo Berbasis Antropometri di PT. XYZ - Ardiansyah, Muhammad Andre; Satoto, Handy Febri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Stitching is an important process in jumbo sack production, which is done semi-manually with one worker per machine. Problems arise because the height of the work chair does not match the dimensions of the worker's body, giving rise to complaints of musculoskeletal disorders (MSDs) in the back and neck. The research results show that workers add hard cushions to chairs, with the aim of adjusting body height requirements. This causes a burning sensation and pain in the buttocks area, this was proven by 11 out of 12 workers who felt the same complaint. This research aims to redesign the jumbo sack sewing work chair based on anthropometric data and percentile calculations using (P5, P50, P95). As a solution, this research proposes designing an ergonomic chair with a minimum seat height of 47 cm and a maximum height of 52 cm, a seat length of 40 cm, a seat width of 40 cm, a backrest height of 52 cm, and a top backrest width of 44 cm. It is hoped that this design can become a reference in making ergonomic chairs to reduce worker complaints.